Association of major blood lipids with post‐stroke dementia: A community‐based cohort study. (26th January 2022) - Yang, Zhirong; Edwards, Duncan; Burgess, Stephen; Brayne, Carol; Mant, Jonathan
Abstract: Background and purpose: The roles of blood low‐density lipoprotein cholesterol (LDL‐C), high‐density lipoprotein cholesterol (HDL‐C) and triglycerides in the development of post‐stroke dementia remain uncertain. This study was to investigate their potential associations. Methods: A retrospective cohort study was conducted using the Clinical Practice Research Datalink. Patients with first‐ever stroke but no prior dementia were followed up for 10 years. Cox regression was used to examine the association of baseline LDL‐C, HDL‐C and triglycerides with post‐stroke dementia. Results: Amongst 63, 959 stroke patients, 15, 879 had complete baseline data and were included in our main analysis. 10.8% developed dementia during a median of 4.6 years of follow‐up. The adjusted hazard ratio of dementia for LDL‐C (per log mmol/l increase) was 1.29 (95% confidence interval [CI] 1.14–1.47), with a linear increasing trend ( p trend <0.001). The counterpart for triglycerides was 0.79 (95% CI 0.69–0.89), with a linear decreasing trend ( p trend <0.001). For HDL‐C, there was no association with dementia (adjusted hazard ratio 0.89, 95% CI 0.74–1.08) or a linear trend ( p trend = 0.22). Conclusions: Blood lipids may affect the risk of post‐stroke dementia in different ways, with higher risk associated with LDL‐C, lower risk associated with triglycerides, and no association with HDL‐C. Abstract : Blood lipids may affect the risk of post‐stroke dementia in different ways, with higher risk associated with low‐density lipoprotein cholesterol, lower risk associated with triglycerides, and no association with high‐density lipoprotein cholesterol.